Impact of spirulina supplementation on obesity-related metabolic disorders: a systematic review and meta-analysis of randomized controlled trials - Bohórquez Medina, Sofía L. (2021)
Spirulina is a cyanobacterium rich in proteins, polyunsaturated fatty acids, and bioactive compounds, such as C-phycocyanin, which has anti-inflammatory and antioxidant properties and possible lipid and glucose metabolism effects. This systematic review aimed to analyze the effects of spirulina on lipid profile, glucose metabolism, and anti-inflammatory markers (CRD42018097156). After systematically searching for randomized controlled trials evaluating spirulina supplementation in adults with obesity, diabetes, or dyslipidemia on Scopus, Embase, PubMed/MEDLINE, Web of Science, and Cochrane Library databases and assessing the risk of bias (Rob 2.0), a random-effects meta-analysis (Mean Difference, CI 95%) was conducted on seven selected articles (n = 338). We found that spirulina supplementation significantly reduced the triglycerides (TG) (mean difference (MD): −15.34 mg/dL; 95% CI: −29.76 to −0.91) and total cholesterol (TC) levels (MD: −11.83 mg/dL; 95% CI: −20.56 to −3.10). However, low-density lipoprotein cholesterol (LDL-C) (MD: −7.80 mg/dL; 95% CI: −16.94 to 1.33), fasting blood glucose (FBS) (MD: −3.38 mg/dL; 95% CI: −9.88 to 3.12), and glycosylated hemoglobin (HbA1c) (MD: −0.27%; 95% CI: −0.94 to 0.39) levels were not significantly reduced. High-density lipoprotein cholesterol (HDLsingle bondC) (MD: 0.73 mg/dL; 95% CI: −2.49 to 3.94) was also increased but not significantly. Spirulina supplementation resulted in a decrease in TG and TC levels; it improved the lipid profile of patients with type 2 diabetes, metabolic syndrome, overweight, or obesity, showing its significant role as an adjuvant treatment.